Recent Development of Nanofibers in Medical/Pharmaceutical Sectors - Khulbe, KC; Matsuura, T; Savoji, H (Archives of Surgery and Clinical Research, 2025)
This article provides a comprehensive overview of the properties, applications, and fabrication techniques of nanofibers, which are characterized by their ultrafine diameters and unique features such as high surface area and aspect ratio. These attributes render nanofibers particularly advantageous for a wide range of applications, especially in the biomedical sector, encompassing areas like tissue engineering, drug delivery, and wound dressing. The article highlights various studies that illustrate the potential of nanofibers in addressing healthcare challenges, particularly their utilization in scaffolds for regenerative medicine and as carriers for controlled drug delivery. Furthermore, it discusses different preparation methods for nanofibers, including electrospinning and alternative techniques, while stressing the importance of polymer selection in achieving optimal drug-release properties. The article also delves into the application of nanofibers in tissue engineering, specifically for bone, cartilage, and vascular applications, and examines their emerging roles in organ-on-a-chip technology and contraceptive development. In conclusion, the article emphasizes the versatility and significance of nanofibers in advancing medical technologies and their potential to address contemporary health challenges. Collaborative efforts between material scientists and biologists are essential to foster interdisciplinary research aimed at improving electrospinning methodologies.